Biomechanics and motor control of early acceleration: enhancing the initial sprint performance of professional rugby union backs - Wild, J. (St. Mary`s University, Twickenham, 2022)
Sprint acceleration is an important performance feature in many sports. For professional rugby union backs, short distance sprints are frequently carried out in training and competition, but how technique and strength-based characteristics contribute to their acceleration performance during these initial steps is not currently well understood. A series of investigations were therefore undertaken to, firstly, advance the understanding of this area and, secondly, to apply this information by prescribing individual-specific interventions to enhance initial acceleration performance. Three initial investigations sought to determine how technical features and strength-based qualities of professional rugby union backs related to their sprint performance (quantified as normalised average horizontal external power) during the initial steps. Findings from these investigations highlighted that focussing on the contribution of discrete technical variables to acceleration performance in isolation is an overly reductionist approach which overlooks how complex systems achieve high sprint performance. Findings also highlighted how important information on individuals can be lost using group-based study designs, since different inter-athlete strategies were adopted to achieve similar performance outcomes. In the fourth investigation, four sub-groups of participants were identified, using cluster analysis, based on their whole-body kinematic strategies. At the intra-individual level, the variables which portrayed their individual strategies remained stable (CV: 1.9% to 6.7%) across multiple separate occasions. This characterisation of whole-body strategies was used to develop a novel and rigorous approach to longitudinally assess the efficacy of technical-based acceleration interventions. Demonstrating the application of this approach in the final investigation, several individual-specific interventions were prescribed to professional rugby union backs based on within-individual relationships of their technique strategies and strength-based capabilities with acceleration performance. Changes in within-individual technique and acceleration performance were measured at multiple time points across an 18-week intervention period where meaningful enhancements in acceleration were observed. This demonstrated that individual-specific technical interventions were effective in manipulating aspects of acceleration technique and performance. The outcome of these investigations provides a novel approach for practitioners working to individualise sprint-based practices.